A calixarene-based coordination cage as an efficient luminescent sensor for Fe3+, MnO4−, NB and 2, 4-DNP in aqueous medium. Issue 10 (14th February 2023) - Zhang, Jiamao; Deng, Yue; Wang, Shentang; Yang, Jun; Hu, Shanshan
Abstract : A luminescent coordination cage formulated as {Mg24 (TC4A)6 (BTC)8 (H2 O)6 } (SWU-2, H4 TC4A = p-tert -butylthiacalix[4]arene, H3 BTC = 1, 3, 5-benzenetricarboxylic acid) was successfully synthesized by the assembly of Mg4 -TC4A units with BTC ligands. Abstract : A luminescent coordination cage formulated as {Mg24 (TC4A)6 (BTC)8 (H2 O)6 } (SWU-2, H4 TC4A = p-tert -butylthiacalix[4]arene, H3 BTC = 1, 3, 5-benzenetricarboxylic acid) was successfully synthesized by the assembly of Mg4 -TC4A units with BTC ligands. SWU-2 shows excellent fluorescence characteristics in aqueous solution and in the solid state. Luminescence sensing experiments indicated that SWU-2 exhibits obvious fluorescence quenching for Fe 3+, MnO4, − nitrobenzene (NB) and 2, 4-dinitrophenol (2, 4-DNP) in aqueous medium and can be regarded as a high sensitivity sensor for detecting Fe 3+, MnO4 −, NB and 2, 4-DNP.